The development of China and its impact on the world economy - Söderlund, Leif (MTT, 2005)
China s entry into the World Trade Organization at the end of 2001 after 15 years of negotiations was a landmark event in the history of the world economic system. It has accelerated economic reform in China, leading the country towards a full market economy, and quickened the pace of change in agriculture and in rural areas. China s emergence as a global economic power poses a serious competitive challenge to other major economies, in particular the United States, the EU, Japan and other Asian countries. This macroeconomic study gathers together extensive socio-economic data, notably on trends between 1990 and 2004, and makes a number of important observations on China s economic performance in domestic and international trade and on its social development in matters of rural-urban relations. China will need greater amounts of energy to sustain the growth in its economy in the future, and meeting this increasing demand will be no easy task. The problems caused by rapid industrial growth and urbanisation and their effects on the environment are also explored. The conclusions highlight the socioeconomic issues that call for further policy reforms on the part of the Chinese government.
Keywords: Ys; taloudellinen vaikutus; Kiina; markkinatalous; kansainvälinen kauppa; tuloerot; maaseutu; kaupunki; market economy; international trade; FDI; rural-urban disparities